Teens and Sleep - Donna Davis (EDIS, 2012)
“Keeping up with the daily schedule of a teenager can be exhausting. However, they are often the ones who are truly suffering! …” This transcript of a two-minute Family Album Radio broadcast was published by the UF Department of Family, Youth and Community Sciences, March 2012.